Penyuluhan Pendidikan Dalam Meningkatkan Minat Santri/Wati Untuk Melanjutkan Pendidikan Ke Perguruan Tinggi - Iqbal Kamil Siregar; Samsul Haq; Nurainun Ritonga; Muhammad Ilyas Nst (STMIK Royal, 2021)
Abstract: Educational Counseling in Increasing the Interest of Santri / wati to Continue Education to Higher Education aims to provide knowledge to students about the Higher Education system and the introduction of several campuses and scholarships provided by the government to encourage the government's mission of entrepreneur santri. Of course, the students have different talents and abilities. So it is necessary to have an approach or self-evaluation of what interests will be chosen to continue to higher education. This counseling opportunity becomes an arena to motivate students to continue their education at higher education. He also explained that lectures are not only related to knowledge but also determine the future which will determine a better life. On this occasion the community service team presented various information including describing what study programs and faculties are available. In addition, what is important information is information related to tertiary entry pathways. There are three pathways described, namely the SMPTN, SBMPTN, SPMB, and achievement pathways. Keywords: education; extension; students. Abstrak: Penyuluhan Pendidikan Dalam Meningkatkan Minat Santri/wati Untuk Melanjutkan Pendidikan ke Perguruan Tinggi bertujuan untuk memberikan pengetahuan kepada santri-santriwati tentang sistem Pendidikan Tinggi dan pengenalan beberapa kampus serta beasiswa yang disediakan pemerintah demi terdorongnya misi pemerintah santri entrepreneur. Para santri tentu memiliki bakat dan kemampuan yang berbeda-beda. Sehingga perlu adanya pendekatan atau evaluasi diri minat apa yang akan dipilih untuk melanjutkan ke perguruan Tinggi. Kesempatan penyuluhan ini menjadi ajang untuk memotivasi para santri untuk bisa melanjutkan pendidikan di perguruan tinggi. Juga menjelaskan bahwa perkuliahan tidak hanya mengejar terkait ilmu tapi menentukan masa depan yang nantinya akan menjadi penentu kehidupan yang lebih baik. Pada kesempatan kali ini tim pengabdian masyarakat memaparkan berbagai infor-masi diantaranya menjabarkan prodi dan fakultas apa saja yang ada. Selain itu yang menjadi infromasi penting adalah informasi terkait jalur masuk perguruan tinggi. Ada tiga jalur yang dipaparkan yakni jalur SMPTN, SBMPTN, SPMB, dan juga jalur prestasi. Kata kunci: pendidikan; penyuluhan; santri.